Insight into the quality deterioration induced by microorganisms in Litopenaeus vannamei during superchilling storage - Chuang Pan; Kaiying Yang; Xianqing Yang; Haiyun Wu; Chunsheng Li; Shuxian Hao; Yongqiang Zhao; Shengjun Chen; Xiaoshan Long (Food Science and Human Wellness)
Quality deterioration induced by microbial community in Litopenaeus vannamei during superchilling storage were demonstrated in this study. In this study, 6 microorganisms were identified as the biomarkers by 16S rDNA sequencing and 71 differential metabolites were identified by untargeted metabolomics. The correlation analysis between microorganisms and differential metabolites revealed that Oceanicaulis, Aliihoeflea, Prauserella, Chelativorans and Pseudoalteromonas had the potential to be the important microorganisms of deterioration of superchilled shrimp. Moreover, the spearman correlation analysis revealed that lightness value had highly significant correlation with Shewanella (P < 0.01), and thiobarbituric acid content, total viable count value, total sulfhydryl content, trichloroacetic acid-soluble peptide and Ca2+-ATPase activity showed significantly correlation with Oceanicaulis, Prauserella, Chelativorans, Aliihoefl ea and Pseudoalteromonas (P< 0.05). This study offers a better understanding for mechanisms behind quality degradation induced by microorganisms, which may help the quality maintaining of Pacific white shrimp during superchilling storage.